Awareness of the citizens from the municipality of Bor on the influence of pharmaceutical waste on human health and environment - Jorgovanović, Sonja; Božić, Dragica; Jorgovanović, Slaviša; Ćurčić, Marijana; Buha Djordjević, Aleksandra; Antonijević Miljaković, Evica; Djukić-Ćosić, Danijela; Javorac, Dragana; Baralić, Katarina; Bulat, Zorica; Antonijević, Biljana (Archives of Pharmacy, 2022)
The rapid global growth of drugs production and consumption undoubtedly leads to contamination of the environment with pharmaceutical substances, as well as the products of their decomposition and metabolism. Therefore, the ecosystem is exposed to pharmaceutical waste, what may result in various unwanted effects, such as the development of microorganism’s resistance to antibiotics. A brief review of the European Union regulations, as well as the United States of America and Australia amadments, revealed the diversity of approaches and regulatory measures adopted with the purpose of proper hazardous waste handling. However, none of proposed systems show enviable results. We conducted the research in the period of March-May 2020, to find out how citizens of Bor municipality handle the pharmaceutical waste. A total of 226 responses were collected by surveying patients, in person and in electronic form. The obtained results were analyzed using the statistical software SPSS 21.0. The presented results show that the awareness of the potential toxicity of pharmaceutical waste is developed in more than a third of respondents (37.5%), but also low level of knowleadge about the proper way of disposing generated waste. Over 36% of men and 42% of women throw away their medicines together with other household waste, while 9% of men and 11% of women take them to pharmacies. The legal regulations and accompanying guidelines, together with appropriate media campaign, would contribute to a better understanding of the given problem and the adoption of new citizens habits when it comes to hazardous waste handling.